A preliminary analysis of feminist views on the crime of rape - Kania, Richard R. E. (American journal of criminal justice, 1983)
Although rape has been considered a serious social problem for centuries, the rise of the Feminist Movement in North America in the 1970’s has served to bring the problem into the public eye. Leading Feminists, among them Camille LeGrand and Susan Brownmiller, have proposed new hypotheses both on rape and the rapist which differ significantly from traditional theories on the crime. Some of the Feminists’ hypotheses, particularly those which presuppose very high levels of rape and assume massive underreporting of the crime by its victims, do not receive much support in empirical surveys. But one aspect of the Feminists’ perspective on rape—that rape is an act against both person and property—is substantiated by empirical analysis of UCR data. The data suggest that the crime of rape shares significant commonalities with the crimes of property, as well as crimes of violence, and rape statistics act to hold together these two, otherwise different, categories of crime.